ARAHAN PENGEMBANGAN KAPAL TRADISIONAL KLOTOK DI PELABUHAN KAMPUNG BARU BALIKPAPAN BERDASARKAN PERSEPEKTIF MASYARAKAT: ARAHAN PENGEMBANGAN KAPAL TRADISIONAL KLOTOK DI PELABUHAN KAMPUNG BARU BALIKPAPAN BERDASARKAN PERSEPEKTIF MASYARAKAT - Dwi Fitrianingsih (ECO-BUILD, 2025)
Balikpapan City and North Penajam Paser Regency are bordered by Balikpapan Bay, so currently access between the two areas is via crossings, one of which is the crossing by klotok boat at Kampung Baru Harbor. Analysis and policy direction are needed to improve the quality of crossing services by klotok boats so that the ease and comfort of mobility increases. This research uses Importance Performance Analysis (IPA) which functions to identify the level of importance and performance of traditional klotok ship crossings. This analysis is carried out as a basis for making policy directions. From the results of the IPA analysis, it was found that the variables whose performance needed to be improved were safety and security